Study of the influence of rapidly quenched aluminum alloy on the wear resistance of ultra-high-molecular-weight polyethylene - Tomina, А.-М.V.; Yakovenko, D.V.; Bashev, V.F.; Golovko, S.I. (Проблеми трибології, 2025)
The article considers the influence of 5-30 wt.% dispersed (50-100 μm) AlMnCrVZrCuMgW alloy rapidly quenched from the liquid state on the wear resistance of ultra-high-molecular-weight polyethylene under different operating conditions. In particular, we studied the behaviour of the metal-polymer composite under the action of rigidly fixed abrasive particles and friction conditions without lubrication according to the “disk-pad” scheme. This simulates real operating conditions in tribological joints of mechanisms of modern machinery. The results of experimental studies showed that introducing the rapidly quenched AlMnCrVZrCuMgW alloy into the composition of the polymer material contributes to a significant improvement in its wear resistance in different modes. Thus, the abrasive wear index decreases 1,7 times compared to pure ultra-high-molecular-weight polyethylene.  The increase in wear resistance is due to the increase in the resistance of the ultra-high-molecular-weight polyethylene surface to mechanical stress. This is confirmed by an increase in the hardness of the material by 1,46 times. Morphological analysis of the friction surfaces revealed a decrease in the number and depth of the ploughing grooves, which is additional confirmation of the effective action of the AlMnCrVZrCuMgW rapidly quenched alloy as a strengthening phase.